Stress Level of Physical Education Students in Writing Thesis - Yahya Eko Nopiyanto; Arwin Arwin; Ari Sutisyana; Yarmani yarmani; Ipa Sari Kardi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The stress experienced by students in writing a thesis can have a negative physical and psychological impact on success in writing a thesis. Therefore, this study aims to determine the level of stress, sources of stress, and types of stress experienced by students. The method used in this research is descriptive quantitative chosen to assist in achieving the research objectives. A total of 23 physical education students who have taken the proposal seminar exam are used as samples in this study. The questionnaire which has a validity value of 0.84 and a reliability value of 0.87 is used as a data collection instruments. The ideal mean value and standard deviation were used to perform data analysis. The results of the study revealed that the stress level of physical education students who were writing their thesis was in the medium category, conflict was the source of stress that had the highest score, and the type of stress experienced by students was psychological stress.